Improving the Thermostability of Rhizopus chinensis Lipase Through Site-Directed Mutagenesis Based on B-Factor Analysis - Jiang, Zhanbao; Zhang, Chengbo; Tang, Minyuan; Xu, Bo; Wang, Lili; Qian, Wen; He, Jiandong; Zhao, Zhihong; Wu, Qian; Mu, Yuelin; Ding, Junmei; Zhang, Rui; et al. (Frontiers in Microbiology, 2020)
In order to improve the thermostability of lipases derived from Rhizopus chinensis, we identified lipase (Lipr27RCL) mutagenesis sites that were associated with enhanced flexibility based upon B-factor analysis and multiple sequence alignment. We found that two mutated isoforms (Lipr27RCL-K64N and Lipr27RCL-K68T) exhibited enhanced thermostability and improved residual activity, with respective thermal activity retention values of 37.88% and 48.20% following a 2 h treatment at 50°C relative to wild type Lipr27RCL. In addition, these Lipr27RCL-K64N and Lipr27RCL-K68T isoforms exhibited 2.4- and 3.0-fold increases in enzymatic half-life following a 90 minute incubation at 60°C. Together these results indicate that novel mutant lipases with enhanced thermostability useful for industrial applications can be predicted based upon B-factor analysis and constructed via site-directed mutagenesis.